The Trader's Behaviour in the Market Period - Stykolt, Stefan; Scott, Anthony (Review of Economic Studies, 1955)
Stefan Stykolt, Anthony Scott; The Trader's Behaviour in the Market Period, The Review of Economic Studies, Volume 23, Issue 3, 1 January 1955, Pages 193–2